Characterization of 7-Methylguanosine Identified Biochemical Recurrence and Tumor Immune Microenvironment in Prostate Cancer - Xin, Sheng; Deng, Yuxuan; Mao, Jiaquan; Wang, Tao; Liu, Jihong; Wang, Shaogang; Song, Xiaodong; Song, Wen; Liu, Xiaming (Frontiers in Oncology, 2022)
Prostate cancer (PCa) has a high incidence rate, mortality rate, and biochemical recurrence (BCR) rate. 7-methylguanosine (m7G), as one of the RNA modifications, has been considered to be actively involved in cancer-related translation disorders in recent years. Therefore, we first used the Cancer Genome Atlas (TCGA) database to identify prognosis and m7G related-lncRNAs. Then we randomly divided the samples into the training set and test set, then constructed and verified the m7G lnRNAs prognostic model (m7Gscore) by the least absolute shrinkage and selection operator (LASSO) regression analysis. m7Gscore has been proved to be the independent marker of BCR-free survival in patients with PCa. Furthermore, m7Gscore was significantly correlated with the tumor immune microenvironment (TIME) and somatic mutation of PCa patients, and had the potential to be the indicator for the selection of drug treatment. We also clustered the TCGA cohort into three m7G-related patterns (C1, C2, and C3). Kaplan–Meier survival analysis revealed that C1 had the best BCR-free survival and C3 had the worst. The TIME was also significantly distinct among the three m7G-related patterns. According to the TIME characteristics of the patterns, we defined C1, C2, and C3 as immune-desert phenotype, immune-inflamed phenotype, and immune-excluded phenotype respectively.